The Relationship between Safety Culture and Safety Behavior: An Approach to Occupational Accident and Injury Management - Mohsen Mahdinia; Ahmad Soltanzadeh; Kiana Hosseinzadeh; Alireza Omidi Oskouei (Shiraz University of Medical Sciences, 2022)
Background: Safety culture can be a good indicator of safety performance which can contribute to the formation of the employee safety behaviors. Therefore, recognizing the dimensions of safety culture and their effect on the employee safety behaviors could be a useful step in the management of occupational accidents. As such, this study was conducted in order to investigate the relationship between safety culture dimensions with employee safety behaviors and accidents, in 2019.Methods: This cross-sectional study was conducted on 315 employees in 19 different industries in one of the central provinces of Iran. Data collection tools included the safety culture and safety behavior questionnaires. Data were analyzed in IBM SPSS 22.0, using independent T-test, logistic regression, multiple linear regressions, and Factor Analysis.Results: The results showed that safety culture had a multidimensional structure, and all of its dimensions had a positive and significant correlation with safety behaviors (P<0.001). In addition, safety culture had a significant inverse correlation with accidents (P<0.05).Conclusion: Management commitment to safety is a key factor in the improvement of employee safety behavior. To reduce accidents and safety problems, it is recommended that the management should focus adequately on the safety policies and procedures.